Resonant inductive decoupling (RID) for transceiver arrays to compensate for both reactive and resistive components of the mutual impedance. (18th June 2013) - Avdievich, Nikolai I.; Pan, Jullie W.; Hetherington, Hoby P.
Abstract : Transceiver surface coil arrays improve transmit performance ( B 1 /√kW) and B 1 homogeneity for head imaging up to 9.4 T. To further improve reception performance and parallel imaging, the number of array elements must be increased with a corresponding decrease in their size. With a large number of small interacting antennas, decoupling is one of the most challenging aspects in the design and construction of transceiver arrays. Previously described decoupling techniques using geometric overlap, inductive or capacitive decoupling have focused on the elimination of the reactance of the mutual impedance only, which can limit the obtainable decoupling to –10 dB as a result of residual mutual resistance. A novel resonant inductive decoupling (RID) method, which allows compensation for both reactive and resistive components of the mutual impedance between the adjacent surface coils, has been developed and verified experimentally. This method provides an easy way to adjust the decoupling remotely by changing the resonance frequency of the RID circuit through the adjustment of a variable capacitor. As an example, a single‐row (1 × 16) 7‐T transceiver head array of n  = 16 small overlapped surface coils using RID decoupling between adjacent coils was built. In combination with overlapped coils, the RID technique achieved better than –24 dB of decoupling for all adjacent coils. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : Transceiver surface coil arrays improve transmit performance and B 1 homogeneity for high‐field head imaging. Decoupling is the most challenging aspect in the design of transceiver arrays. Previously described decoupling techniques have focused on the elimination of the mutual inductance only, which limits the obtainable decoupling as a result of residual mutual resistance. A novel resonant inductive decoupling (RID), which allows compensation for both mutual reactance and resistance between the adjacent antennas, has been developed and verified experimentally.